Energy Harvesting Under Dim-Light Condition With Dye-Sensitized and Perovskite Solar Cells - Juang, Sean Sung-Yen; Lin, Pei-Ying; Lin, Yu-Chiung; Chen, Yu-Sheng; Shen, Po-Shen; Guo, Yu-Ling; Wu, Yu-Chun; Chen, Peter (Frontiers in Chemistry, 2019)
We demonstrate highly efficient energy harvesting devices for dim-light application under 200 lux irradiation using dye-sensitized solar cells (DSCs) and perovskite solar cells (PSCs). The high-efficiency DSCs are composed of cobalt-based redox mediators in 3-methoxypropionitrile (MPN) solvent with MK-2 sensitizer. With introduction of underlayer treatment and fine-tuning of compositions in cobalt-based electrolyte, the power conversion efficiency of cobalt-based DSCs achieves 16.0% under 200 lux illumination. That outperforms the best device using the conventional iodine-based electrolyte illuminated with the same light intensity. Especially, cobalt-based electrolyte system exhibits a higher open circuit voltage than iodine-based electrolyte counterpart. We also investigate perovskite solar cells under dim-light condition. PSCs show higher open circuit voltage and short circuit current density than DSCs with efficiency up to 23.4%. In this work, our results demonstrate promising potential of DSCs and PSCs in the dim-light applications.